Gold catalysis: β-ketonaphthalenes via molecular gymnastics of 1,6-diyne-4-en-3-ols - Lauterbach, Tobias; Arndt, Sebastian; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2013)
1,6-Diyne-4-en-3-ols with one terminal alkyne were applied as test substrates for a possible dual catalyzed cyclization. Instead of a dual catalysis cycle, naphthyl ketone derivatives were obtained as single products. The regioselectivity of the obtained products is unprecedented. Instead of the expected naphthyl ketones bearing the keto group in the α-position, the keto group is positioned in the ß-position of the naphthyl skeleton by a complex rearrangement of the starting materials.